A qualitative analysis of responses to a question prompt list and prognosis and end‐of‐life care discussion prompts delivered in a communication support program. Issue 3 (30th July 2014) - Walczak, Adam; Henselmans, Inge; Tattersall, Martin H. N.; Clayton, Josephine M.; Davidson, Patricia M.; Young, Jane; Bellemore, Frances A.; Epstein, Ronald M.; Butow, Phyllis N.
Abstract Objective Discussing end‐of‐life (EOL) care is challenging when death is not imminent, contributing to poor decision‐making and EOL quality‐of‐life. A communication support program (CSP) targeting these issues may facilitate discussions. We aimed to qualitatively explore responses to a nurse‐led CSP, incorporating a question prompt list (QPL—booklet of questions patients/caregivers can ask clinicians), promoting life expectancy and EOL‐care discussions. Methods Participants met a nurse‐facilitator to explore an EOL‐focussed QPL. Prognosis and advance care planning (ACP) QPL content was highlighted. Thirty‐one transcribed meetings were analysed using thematic text analysis before reaching data saturation. Results Thirty‐one advanced cancer patients (life expectancy <12 months) and 11 family caregivers were recruited from six medical oncology clinics in Sydney, Australia. Intent to use the QPL related to information needs, involvement in care and readiness to discuss EOL issues. Many participants did not want life expectancy estimates, citing unreliable estimates, unknown treatment outcomes, or coping by not looking ahead. Most displayed interest in ACP, often motivated by a loved one's EOL experiences, clear treatment preferences, concerns about caregivers or recognition that ACP is valuable regardless of life expectancy. Timing emerged as a reason not to discuss EOL issues; many maintaining it was too early. Conclusion Patients and caregivers appear ambivalent about acknowledging approaching death by discussing life expectancy but value ACP. Given heterogeneity in responses, individualised approaches are required to guide EOL discussion conduct and content. Further exploration of the role of prognostic discussion in ACP is warranted. Copyright © 2014 John Wiley & Sons, Ltd.